Socket prosthesis manufacturing process made from bamboo fiber composite materials. Issue 1 (July 2020) - Purna Irawan, Agustinus; Wayan Sukania, I; Anggarina, Paula T.; Raditya Danendra, Albertus; Dimas Baskara, Gregorius
Abstract: This research aims to develop the manufacturing process of making socket prosthesis with bamboo fiber composite material and epoxy matrix. Bamboo fiber was chosen because it is strong, environmentally friendly, and recyclable. The focus of research is to arrange the manufacturing process of making sockets, starting from material preparation to socket testing. The method used in this study is a customized method and prototype socket manufacture in accordance with the dimensions obtained from the patient. Based on the results of the research that has been carried out, stages of the manufacturing process, results of compressive strength testing, and morphological analysis of socket products are obtained. These results will be a reference in future research.